2009
DOI: 10.1007/s00520-009-0619-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for late radiation tissue injury in gynaecological patients

Abstract: It is not possible to conclude from our study if gynaecological patients with pelvic pain will benefit from HBOT. The application of HBOT to selected patients may be justified, but further research with adequate sample size, as well as the timing of HBOT related to the development of LRTI, is required to establish the optimum patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A study by Rud et al. (), aiming to reduce pelvic pain after radiation, showed no detectable effect of hyperbaric oxygen therapy, even though some patients experienced relief in overall symptom burden. Finally, Nord et al.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Rud et al. (), aiming to reduce pelvic pain after radiation, showed no detectable effect of hyperbaric oxygen therapy, even though some patients experienced relief in overall symptom burden. Finally, Nord et al.…”
Section: Resultsmentioning
confidence: 99%
“…All patients with vaginal radiation necrosis or rectovaginal fistula experienced complete resolution of necrosis with HBO 2 ; only 1 treatment failure occurred. Other studies have found similarly positive effects and response rates for a range of clinical features of lrti, including proctitis, cystitis, proctitis and other gastrointestinal complications, and pain [22][23][24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…Among women experiencing lrti from treatment for gynecologic malignancies, the response rate to HBO 2 is of the order of 70%. Studies have found positive effects and a range of specific response rates for various clinical features of lrti (including cystitis, proctitis, and other gastrointestinal complications) and pain [23][24][25][26][27] . There is some evidence to suggest that outcomes are better when HBO 2 is initiated by 6 months from the start of symptoms rather than being delayed beyond that point 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations